Denial, acknowledgement and reconciliation - Jamieson Ruth (Temida, 2002)
This paper examines the recent work of professor Stanley Cohen on `states of denial’ and will pay specific attention to his explication of the ways in which the concepts of denial and acknowledgement have been deployed in both mainstream culture and official discourses on truth and reconciliation. The paper tries to assess the extent to which Cohen’s model of denial and acknowledgement offers a potential basis for facilitating reconciliation in the former Yugoslavia. Particular attention will be paid to Cohen’s argument about the dangers inherent in the ‘over-acknowledgement’ of past suffering.